Analyzing The Company’s Work Environment Within the Task Complexity - Rini Purnamasari; Ahmad Abbas; Yana Firana (Almana : Jurnal Manajemen dan Bisnis, 2020)
The job description established in organizational structure is the starting signal to know the firm work environment. If it is operated through a complex job division, the performance quality will not run maximally. This research aims to analyze the work environment through the job description given by the firm. The type of this research is a qualitative under case study approach. This research was conducted in the logistic service firm, namely Sarana Citra Adicarya (SCAc). The data were obtained from the interview, observation, and documentation. The result of this research discloses that the work environment of Sarana Citra Adicarya is less well-integrated, not on time, as well as encourages procrastination so that the employees do not enjoy the job and cannot work for a long time.